A systems psychodynamic description of organisational bullying experiences - Frans Cilliers (SA Journal of Industrial Psychology, 2012)
Orientation: Organisational bullying experiences manifest themselves as an intense unconscious systemic dynamic involving the bully, the victim and the organisational culture. The relatedness between the objects is characterised by valences and mutual defence mechanisms such as splitting, projection and projective identification. Research purpose: The purpose of this research was to describe organisational bullying experiences from the system psychodynamic perspective.